Conceptual model of factors driving the innovative IT cluster development - Pobol, Anna I. (Journal of the Belarusian State University. Economics, 2018)
In the paper, the insights of the concepts on innovative clusters; national innovation systems; networks theory and institutional economy are used to further elaborate the toolbox for studying and fostering the innovative clusters. A set of additional criteria for measuring the qualitative characteristics of development of an innovative cluster along the stages of its lifecycle and an extended conceptual model of factors driving the innovative cluster development specifically for the IT industry are suggested. This model extends over the existing models by delineating the qualitative characteristics of demand such as demand sophistication, risk-tolerance and innovativeness; specific resources such as networks and professional services; multiple factors of the industry structure such as critical mass of enterprises and employment, degree of specialization, advanced business practices and innovative business models and factors of qualitative shift such as tacit knowledge and R&D results. Attention is put to informal linkages; service infrastructure factors and institutional environment as well. The role of cluster-forming agents in the cluster development is specified. The suggested model can be used as a framework for elaborating the strategy of IT cluster development and for refining the list of appropriate policy measures.